MILTON FRIEDMAN - LIFE AND SCIENTIFIC CONTRIBUTIONS - Jovanović, Milan (Economic Outlook, 2022)
The text is about the life and work of one of the most influential economists of the last century - Milton Friedman. The paper discusses some of Friedman’s greatest contributions to economic theory and practice, starting with the earliest life of Milton Friedman, and the historical circumstances that were of decisive influence on his life. An analysis of several of Friedman’s most significant works, written mainly in the years spent at the University of Chicago, examines Friedman’s contribution to economic theory. Friedman’s contribution to the reaffirmation of quantitative money theory and consumption analysis, controversial interpretation of the causes of the Great Depression, critique of the Phillips curve, with reference to the Keynesian-monetarist debate and Friedman’s contribution to the methodology of economics are discussed. The last part of the paper presents the position on Friedman’s socio-political influence on a global level. There is talk of Friedman’s contribution to strengthening the concept of liberalism, affirmation of the ideas of the free market, individual freedom and personal integrity, while reducing the regulatory role of the state in the economy.